Relative age effect, skeletal maturation and aerobic running performance in youth soccer players - Teixeira,Anderson Santiago (2018)
Abstract Aims: To investigate the presence of a relative age effect (RAE) and the influence of birth quarters (BQ), semesters (S) as well as skeletal maturation on anthropometric characteristics and aerobic peak speed (PST-CAR) in youth male soccer players. Methods: One hundred players were recruited to participate in this study. Players were allocated into 4 BQ’s and 2 S. Skeletal maturity status was assessed using the Fels method. Assessments for players included determination of body size and composition and PST-CAR. Results: Overall, more players were born in BQ1 (38 %) and S1 (75%). The likelihood of players born in BQ1 and BQ2 being selected was 3.61 to 4.96 times higher than players in BQ3 and BQ4. Players in BQ4 maturing earlier were biologically older than their peers in BQ1. The players in BQ3 and S2 displayed higher PST-CAR compared with players in BQ2 and S1, respectively. However, players of contrasting skeletal maturity status did not differ in aerobic performance. Conclusion: Our findings indicate that coaches and talent scouts are systematically retaining average and early maturing players born in S1 and excluding late maturing players born in BQ4. However, aerobic performance appeared to be dependent on the relative age, but independent of skeletal maturation during puberty.